Waterbird occurrence and abundance in the Strobel Plateau, Patagonia, Argentina - Lancelotti, Julio Lucio (2009)
The Strobel Plateau is a conspicuous and representative basaltic plateau (“meseta”) in the Patagonian steppe, Argentina. This plateau is dotted with more than 1500 shallow lakes, which are regularly used by waterbirds and support one of the main breeding populations of the near threatened Hooded Grebe (Podiceps gallardoi). We collected data on bird presence and abundance in 41 shallow lakes, covering a wide spectrum of the wetland environmental variability found in the area. We conducted six surveys from spring to fall between 2004 and 2006. We recorded a total of 18 waterbird species, which represent 5 different families. Anatidae was the family most represented with 12 species, accounting for 85% of the observed waterbirds. Waterbird distribution among lakes was variable, from 2.4% occupied lakes for Wilson’s Phalarope (Steganopus tricolor) and Andean Ruddy-Duck (Oxyura jamaicensis) to 80% for Black-necked Swan (Cygnus melanocorypha), and abundance varied greatly both between species and seasons. The Hooded Grebe, in particular, was recorded in 14 lakes (1–81 individuals). Six species were detected breeding in the area: Hooded Grebe, Silvery Grebe (Podiceps occipitalis), Flying Steamer-Duck (Tachyeres patachonicus), Crested Duck (Anas specularioides), Upland Goose (Chloephaga picta), and White-winged Coot (Fulica leucoptera). The Hooded Grebe nested at four lakes, three of them not previously known to hold breeding birds. Results point to the need of further studies on the dynamic nature of waterbird lake use to adequately assess the importance of the Strobel Plateau as waterbird habitat.